The durability of modified silica/polypropylene nanocomposites : weathering resistance and creep behavior
In this research, the modified silica (SiO2)/polypropylene (PP) nanocomposites were prepared. The accelerated weathering and creep behavior of nanocomposites were investigated. Neat PP with 2 wt% of nanosilica and 3 wt% of modifiers (aminopropyl triethoxysilane (APTES), polypropylene grafted maleic anhydride (PP-g-MA) and polypropylene-methyl polyhedral oligomeric silsesquixone (PP-POSS)) were melt blended in the internal mixer Brabender with rotor speed 60 rpm for 10 minutes. The nanocomposites characterizations were determined by Fourier transform infrared analysis (FTIR) and field emission scanning electron microscope (FESEM). While the mechanical properties of the nanocomposites were determined using a tensile test instrument according to ASTM D638 and thermal behavior through thermalgravimetric analysis (TGA) and differential scanning calorimetry (DSC), respectively, before and after exposure to accelerated weathering test (AWT). The durability behavior of nanocomposites was tested under creep test instrument according to ASTM D2990. From the FTIR analysis, weathered nanocomposites with the PP-POSS showed less carbonyl group which related to the degradation phenomenon to the material comparing to the nanocomposites with APTES, PP-g-MA and without modifiers. Moreover, FESEM images showed less cracking and deformation on the tensile fractured surface of weathered nanocomposites with PP-POSS validating the efficiency of the modifiers. While, from tensile results, the weathered nanocomposites especially with the presence of PP-POSS followed by PP-g-MA and APTES have higher tensile strength but moderate reduction in elongation at break than the weathered nanocomposites without the modifiers. In the terms of thermal behavior, PP-POSS showed good thermal stability compared to other nanocomposites. While for the durability test, the presence of modifiers in the modified silica/PP nanocomposites exhibited good resistance to the creep. PP-POSS provided better improvement creep resistance compared to the nanocomposites with PP-g-MA, APTES and without modifier. This can be concluded that the addition of modifiers improved the weather resistance and creep resistance of nanocomposites.